Competências de gestores de um hospital universitário federal - Renata Cristina Rocha Batista (2019)
The performance of university hospital managers involves different situations, resulting from the complexity of a tertiary hospital, variety of activities and sectors, installed capacity, social responsibility, scarce resources and functions of providing conditions for teaching, research and assistance. For this reason, hospital managers need in their daily actions to mobilize their skills to meet expectations and perform their duties. The aim of this study was to analyze the profile and skills mobilized by managers at a Federal University Hospital. It is a descriptive case study, which chose the concept of competence as a set of knowledge, skills and attitudes (CHA). The study scenario was the Hospital das Clínicas of the Federal University of Minas Gerais, located in the city of Belo Horizonte, Minas Gerais. Data were collected between April and June 2019, through a questionnaire identifying the participants' sociodemographic profile and questions about the skills mobilized by managers. Participated in the study, 31 managers of functional units of assistance, administrative and teaching and research sectors. The data were collected using the online platform (eSurvey). For data analysis, descriptive statistics with absolute and relative frequency of information was used. The results show that the majority of managers are aged between 30 and 40 years old, are health professionals, female, have a university degree for less than 10 years, previous management experience, work in the administrative area, have been in the management position for under 5 and manages between 1 and 50 people. Among the most mobilized skills are: knowledge related to the institution's mission and objectives; human Resources; norms and procedures and management of work processes. Skills such as ethics with staff, superiors and users, problem identification and communication were the most mobilized. The most mobilized attitudes were to be fair to your team and users and to be involved with the work and the team. It is concluded that hospital managers, from the studied public teaching and research institution, have different profiles, mobilize more skills related to skills and attitudes and less related to knowledge in their daily work and due to the nature of the scenario, they are still far from the established precepts.